PERAN KEPALA SEKOLAH DALAM MENERAPKAN BUDAYA INDUSTRI PADA IMPLEMENTASI PROGRAM TEACHING FACTORY : Studi Kasus di SMK Raden Umar Said Kudus - Lousiana Dwinta Utami, - (2019)
Revolusi Industri 4.0 menuntut kompetensi dan pola pekerjaan yang selalu berubah-ubah seiring dengan perkembangan teknologi dan informasi. Di lain sisi, lulusan SMK yang harusnya menghasilkan tenaga kerja terampil justru menjadi penyumbang angka pengangguran tertinggi karena kompetensi yang dimiliki tidak sesuai dengan kompetensi yang dibutuhkan oleh industri. Penelitian ini bertujuan untuk menganalisis peran kepala sekolah dalam penerapan budaya industri pada implementasi program teaching factory. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus tunggal terhadap SMK Raden Umar Said jurusan Animasi. Hasil penelitian menunjukkan bahwa implementasi teaching factory dimulai dari visi kepala sekolah yang kemudian diterapkan dengan kebijakan-kebijakan kepala sekolah untuk melakukan perubahan budaya. Adapun visi kepala sekolah yaitu memperoleh output lulusan yang terserap di industri relevan dengan mengarahkan pembelajaran untuk menghasilkan portofolio pada kompetensi spesifik yang menjadi pilihan peserta didik. Strategi yang dilakukan oleh kepala sekolah yaitu dengan integrasi orang luar, bujukan teknologi, merger, dan promosi subbudaya tertentu. Artifak yang dibentuk yaitu dengan memenuhi 7 parameter teaching factory sebagai bentuk fisik dan 5 budaya industri sebagai bentuk proses. ------- The Industrial Revolution 4.0 requires competencies and pattern of works that are always changing along with the development of technology and information. Industries that are always developing need workers who meet competencies that are in line with current needs. On the other hand, SMK graduates who are supposed to produce skilled workers actually contribute the highest unemployment rates because their competencies do not match the competencies required by the industry. Teaching factory which should be a medium to train students' industrial culture has not been run on the basis of collaboration between schools and industry. This study aims to analyze the role of the principal in the application of industrial culture in the implementation of the teaching factory program. This study uses a qualitative approach with a single case study method to Vocational School Raden Umar Said majoring in Animation. The analysis of this study was carried out with a typology analysis using a cultural level model by Edgar Schein consisting of artifacts, values, and basic assumptions. The results showed that teaching factory implementation was started from the principal's vision which was then translated through a culture change strategy in order to be able to apply industrial culture during teaching factory learning. The principal's vision is to obtain the output of graduates absorbed in relevant industries by directing learning to produce portfolios on specific competencies chosen by students. The strategy undertaken by the principal is by integrating outsiders, technological persuasion, mergers, and promotion of certain sub-cultures. The artifacts formed are by fulfilling 7 parameters of teaching factory as a physical form and 5 industrial cultures as a form of process.